Frontoethmoidal encephaloceles: literature review (Research, Society and Development, 2023)
Encephalocele is a disease with a congenital characteristic, when related to a defect in the neural tube and formation of hernial sacs that vary in composition and are formed externally to the skull as a result of some bone defect or acquired, as a result of trauma, tumors and iatrogenic injuries. Its type varies according to the location of the alterations. The etiology of this pathology is still not very clear. Given the scarcity of up-to-date studies on this topic, this work is a literature review that aims to contribute, based on a literature review, by bringing together the main findings of this pathology, integrating clinical, radiological and therapeutic. A narrative literature review was carried out in March and April 2023, through a database search: PubMed, SciELO and Google Scholar. The descriptors used were Frontoethmoidal encephaloceles, Frontoethmoidal encephaloceles diagnosis and Frontoethmoidal encephaloceles radiology filtered in the last 10 years. Its diagnosis can be made through methods such as MRI in T1 and T2 weighted sequences in sagittal, axial, coronal and FLAIR planes, in addition to CT. Pictures of anterior encephalocele may also present with nasal obstruction, nasal cleft, CSF rhinorrhea, telecanthus and orbital anomaly. Therefore, when we analyze the manifestations found in frontoethmoidal encephalocele, we can infer that it is extremely important to recognize the clinical signs of this pathology, as well as encourage further studies to clarify the subject in question.